Generalized nonlinear model describing softening and hardening behaviors of skin friction for axially loaded piles. (December 2019) - Xu, Ling-Yu; Cai, Fei; Pan, Jing-Min; Xue, Ying-Ying
Abstract: This study proposes a new generalized nonlinear (GN) model to provide a continuous describing in the whole nonlinear regime of load-transfer curves, including both softening and hardening phenomenon. The applicability of the proposed GN model is verified by comparing the calculated relation between the skin friction and relative pile-soil displacement of axially loaded piles with measurements and those calculated by existing nonlinear softening models. Moreover, the proposed GN model is implemented in a finite element program for settlement analysis of axially loaded piles. The results indicate that the proposed GN model can be considered as a generalization of a hyperbolic model and an existing generalized nonlinear softening model and is expected to cover a wide range of variations in skin friction-displacement data of axially loaded piles.